Understanding Breast Cancer Genetics - Zimmerman, Barbara T. (Book collections on Project MUSE., 2004)
Health & Sickness -- Consumer Health -- & . This book by a scientist whose background is in cellular and molecular biology examines the fearsome disease that strikes one in eight women in the United States. Although women are more likely to die of heart disease or of lung cancer, a diagnosis of breast cancer is the medical pronouncement that a woman is most likely to fear. It kills more than 40,000 Americans annually. Why are some women more vulnerable than others? The interplay between genetics and environment is suspected. Thus this book for general readers will help them understand the geneti.